Evaluation of genotoxic effect of X-rays on oral mucosa during panoramic radiography - Mahima Sandhu; Vinay Mohan; Jyothi Shiva Kumar (Wolters Kluwer Medknow Publications, 2015)
Introduction: X-rays are potent mutagenic agents capable of inducing both gene mutations and chromosomal aberrations. They act directly on the DNA molecule or indirectly through the formation of reactive compounds that interact with this molecule. In spite of their mutagenic potential, this kind of radiation is an important tool for diagnosis. Aim: The aim of this study is to analyze the genotoxic effects on oral mucosa during conventional and digital panoramic radiography. Objectives: 1. To assess the nuclear abnormalities, mainly micronuclei in exfoliated buccal mucosal cells, before X-ray exposure and 10 days after exposure using conventional and digital panoramic radiography. 2. Comparison of micronuclei count obtained during conventional and digital panoramic radiography. Materials and Methods: One hundred healthy individuals were chosen who were free of all deleterious habits. Epithelial buccal cells were obtained with an exfoliative cytobrush immediately before exposure and 10 days after exposure. The smears were stained using Giemsa stain and analyzed under low-power and high-power microscope. Results: There was a significant difference in the mean values obtained pre- and post-exposure to conventional panoramic radiography, as the mean value of micronuclei before exposure was 0.025 ± 0.01 which increased to 0.064 ± 0.02 post-exposure. Similarly, there was a significant difference in the mean values obtained pre- and post-exposure to digital panoramic radiography, as the mean value of micronuclei before exposure was 0.022 ± 0.01 which increased to 0.041 ± 0.01 post-exposure. In the present study, there was a highly significant increase in the number of micronuclei post-exposure in conventional panoramic radiography when compared to digital panoramic radiography. Conclusion: This results show that panoramic radiography does induce genotoxic effects in buccal epithelial cells and should be used only when indicated, and that digital panoramic radiography is safer as compared to conventional radiography.